Successful Management of Diabetes Mellitus (Madhumeha) With Ayurvedic Modalities (Vaman & Madhutailik Basti) – A Case Study: Life Sciences -Ayurveda - Balpande, Khushhali; Wajpeyi, Sadhana Misar (International Journal of Life Science and Pharma Research, 2023)
Ayurveda, an ancient medical system, is becoming more popular as a supplemental and alternative therapy for treatingchronic illnesses. Type 2 diabetes is a chronic condition with serious long-term effects on both the people who have it and thehealthcare system as a whole. Ayurvedic classics have twenty types PramehaKaphaj prameha 20, Pittaja prameha 6, and Vatajaprameha 4. Among this type, Diabetes mellitus is compared with Madhumeha, which is one of the Vataja types of Prameha. It is aKledapradhan vyadhi which is associated with excessive urination. The primary causes of the illness are an excessive intake ofdairy products, sugar products, rice, and seafood, an excessive amount of sleep, and a lack of activity. Various complications ofDiabetes mellitus include nephropathy, neuropathy, retinopathy, and cardiovascular disease. A 51-year-old female patient visitedOPD with chief complaints of Sweetness in her mouth, excessive hunger, thirst, urine, and burning sensation at the sole formore than 3 months, and other associated complaints were excessive mental stress and lethargy for the last 1 month. She wastreated with panchakarma treatment like Vaman, Madhutailik basti, and Shaman chikitsa like Nishamalaki churna and Madhunashinivati. Reduction in blood sugar level was observed at the end of treatment. Hence it can be concluded that shodhan and shamanchikitsa is beneficial in treating symptoms of Madhumeha.